Study of Living Hadith on Social Practices in The Framework of The Itba'ul Janāzah Tradition in Kauman Village - Asrul Asrul; Mahatva Yoga Adi Pradana; Achmad Dahlan (Jurnal Living Hadis, 2022)
Researchers see a reality where the tradition of burying the dead in a religious system that is part of the rituals that occur in several religious groups. The itbā'ul janāzah tradition is part of the religious system built by the Muslim community. Kauman village has its own tradition of delivering corpses as a form of religious behavior. This study uses a qualitative type with a living hadith study approach. Researchers see that this tradition is received by hadiths related to the obligation of Muslims to deliver corpses for others. There are two types of hadith that are used as theological references in carrying out itbā'ul janāzah activities in the village of Kauman. First, the narration of Bukhari (1164) sourced from Abu Hurairah about the rights and obligations of every Muslim over other Muslims. Second, the narration of Muslim (1572) which is sourced from Abu Hurairah about the reward of delivering the corpse. From the results of this study, it was concluded that religious practices carried out by the Kauman community were indirectly based on the itbā'ul janāzah hadith.